2006
DOI: 10.1186/1471-2474-7-33
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of measures of impairments associated with patellofemoral pain syndrome

Abstract: Background: The reliability and measurement error of several impairment measures used during the clinical examination of patients with patellofemoral pain syndrome (PFPS) has not been established. The purpose was to determine the inter-tester reliability and measurement error of measures of impairments associated with PFPS in patients with PFPS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
179
1
7

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(215 citation statements)
references
References 63 publications
5
179
1
7
Order By: Relevance
“…However, while statistically significant, Pearson correlation coefficients and corresponding R 2 values were of relatively small magnitude and the meaning of the correlations should be interpreted cautiously. The poor correlation between Q angle and knee stiffness may be related to the less than perfect reliability of the method used for determining Q angle in this study (Piva et al, 2006). Though the procedure used in this study is simple to implement, assessing frontal plane joint alignment via radiographic techniques may lead to more accurate and reliable measurements (Rauh et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, while statistically significant, Pearson correlation coefficients and corresponding R 2 values were of relatively small magnitude and the meaning of the correlations should be interpreted cautiously. The poor correlation between Q angle and knee stiffness may be related to the less than perfect reliability of the method used for determining Q angle in this study (Piva et al, 2006). Though the procedure used in this study is simple to implement, assessing frontal plane joint alignment via radiographic techniques may lead to more accurate and reliable measurements (Rauh et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…For measurement of the Q angle, subjects were supine with the knee extended and leg muscles relaxed. Using a previously described procedure by Piva et al (2006), a trained physical therapist palpated the tibial tubercle, center of the patella, and ASIS and marked their locations using washable ink. A universal goniometer was used to measure the acute angle formed by the lines connecting these bony landmarks.…”
Section: Subjectsmentioning
confidence: 99%
“…13 In subjects with PFPS, Piva et al 19 reported acceptable levels of interrater reliability with ICC 2,2 values (95% confidence interval) of 0.85 (0.68-0.93) for HHD measurements of hip abduction strength in sidelying and 0.79 (0.56-0.91) for HHD measurements of hip external rotation strength in prone.…”
Section: Self-administered Anterior Knee Painmentioning
confidence: 99%
“…Thus, a static measure is used to infer the dynamic condition of PF maltracking. Q-angle intrarater and interrater reliability has varied across studies, with intraclass correlation coefficients reported from 0.20 [12] to 0.70 [34]. Past studies have revealed a correlation [16] and no correlation [32] between Q-angle and PF pain syndrome.…”
Section: Introductionmentioning
confidence: 99%